Dynamic characteristics of enhanced Al/PTFE and real-time quantitative evaluation of impact release energy under vacuum environment - Enling Tang; Zhimin Sun; Yafei Han; Wenhao Yu; Chuang Chen; Mingyang Xu; Mengzhou Chang; Kai Guo; Liping He (Results in Physics, 2021)
Aluminum/Polytetrafluoroethylene (Al/PTFE) reactive material occurs chemical reaction and release a large amount of energy under the impact load, which has the dual characteristics of strength and energy release, so it can be applied to the attack of confined space targets to enhance the damage effect on the target. In order to study the dynamic strength of enhanced Al/PTFE and the real-time impact release energy, based on the traditional formula Al/PTFE (26.5%/73.5%), enhanced Al/PTFE reactive material specimens were prepared by cold pressing and rapid cooling processes, and the dynamic mechanical properties of the specimens were tested by the Split Hopkinson Pressure Bar (SHPB) testing system. The experiments have been conducted by using two-stage light gas gun loading system combining with the impact release energy related testing system under vacuum condition. Meanwhile, the evolutionary process of reaction product was numerically simulated by ANSYS/Fluent, and the boundary conditions of the numerical simulation were defined by self-programmed UDF subroutine. Experiments, theoretical analysis and numerical simulation were adopted to obtain the real time energy release of Al/PTFE reactive materials at different impact velocities. The results show that the maximum dynamic failure strength of the enhanced Al/PTFE reactive projectile is 126 MPa, and the strain rate hardening phenomenon and viscoelastic effect are exhibited when the strain rate is in the range of 1500 ∼ 3000 s−1. When the strain rate is in the range of 3000 ∼ 4000 s−1, the specimen is insensitive to strain rate. When the impact velocities are 2.30 km/s and 2.54 km/s, the energies that the reactive projectiles release are 8.36 kJ/g and 8.38 kJ/g, respectively, and the reactive material reacts completely. When the impact velocities are 1.64 km/s, 1.80 km/s and 1.94 km/s, the projectiles have not fully reacted. The reactive degree of the reactive projectile increases with the increase of the impact velocity. For the complete reaction of Al/PTFE reactive projectile, the critical impact velocity of the enhanced reactive material is between 1.94 km/s and 2.30 km/s.